Effect and mechanism of rare Earth and alkaline Earth metals on the high-temperature stability of activated alumina - Wu, Zhiqiang; Jiang, Longwen; Dong, Quan; Gao, Qiang; Cai, Jingxuan; Cheng, Xiaowei (Frontiers in Materials, 2023)
Active Al2O3 is one of the carrier materials used for the purification of automobile exhaust. The crystal transformation of active Al2O3 is due to the high temperature of the automobile exhaust port, which greatly reduces the specific surface area and affects the catalytic efficiency. To improve the high-temperature stability of active Al2O3, this article synthesized Al2O3 via the gel-sol method. The influence of rare earth and alkaline earth metal doping modification on the high-temperature stability of activated Al2O3 was investigated. The samples were analyzed using Brunauer–Emmett–Teller, X-ray diffraction, Fourier-transform infrared spectroscopy, Scanning electron microscopy, and transmission electron microscopy to explore the effects and mechanism of different contents of La, Ce, and Ba on active Al2O3. The results showed that suitable single doping of La, Ce, and Ba inhibited the phase transition of Al2O3 and improved the high-temperature stability of active Al2O3. When 1% of La and Ba were mixed and doped into active Al2O3, the specific surface area of the sample after aging at 1100°C for 4 h was 119.2512 m2/g. X-ray diffraction analysis revealed the agglomeration of Ba atoms inside the alumina and that the incorporated La atoms accelerated the agglomeration and promoted the formation of BaAl2O4.